Evaluating the impact of post-trial implementation of RHIVA nurse-led HIV screening on HIV testing, diagnosis and earlier diagnosis in general practice in London, UK. (February 2020) - Leber, Werner; Panovska-Griffiths, Jasmina; Martin, Peter; Morris, Stephen; Capelas Barbosa, Estela; Estcourt, Claudia; Hutchinson, Jane; Shahmanesh, Maryam; El-Shogri, Farah; Boomla, Kambiz; Delpech, Valerie; Creighton, Sarah; et al.
Abstract: Background: UK and European guidelines recommend HIV testing in general practice. We report on the implementation of the Rapid HIV Assessment trial (RHIVA2) promoting HIV screening in general practice into routine care. Methods: Interrupted time-series, difference-in-difference analysis and Pearson-correlation on three cohorts comprising 42 general practices in City & Hackney (London, UK); covering three periods: pre-trial (2009–2010), trial (2010–2012) and implementation (2012–2014). Cohorts comprised practices receiving: "trial intervention" only ( n  = 19), "implementation intervention" only ( n  = 13); and neither ("comparator") ( n  = 10). Primary outcomes were HIV testing and diagnosis rates per 1000 people and CD4 at diagnosis. Findings: Overall, 55, 443 people were tested (including 38, 326 among these cohorts), and 101 people were newly diagnosed HIV positive (including 65 among these cohorts) including 74 (73%) heterosexuals and 69 (68%) people of black African/Caribbean background; with mean CD4 count at diagnosis 357 (SD=237). Among implementation intervention practices, testing rate increased by 85% (from 1·798 (95%CI=(1·657, 1·938) at baseline to 3·081 (95%CI=(2·865, 3·306); p  = 0·0000), diagnosis rate increased by 34% (from 0·0026 (95%CI=(0·0004, 0·0037)) to 0·0035 (95%CI=(0·0007, 0·0062); p  = 0·736), and mean CD4 count at diagnosis increased by 55% (from 273 (SD=372) to 425 (SD=274) cells per μL; p  = 0·433). Implementation intervention and trial intervention practices achieved similar testing rates (3·764 vs. 3·081; 6% difference; 95% CI=(-5%, 18%); p  = 0·358), diagnosis rates (0·0035 vs. 0·0081; -13% difference; 95%CI=(-77%, 244%; p  = 0·837), and mean CD4 count (425 (SD=274) vs. 351 (SD=257); 69% increase; 95% CI=(-61%, 249%); p  = 0·359). HIV testing was positively correlated with diagnosis ( r  = 0·114 (95% CI=[0·074, 0·163])), and diagnosis with CD4 count at diagnosis ( r  = 0·011 (95% CI=[-0·177, 0·218])). Interpretation: Implementation of the RHIVA programme promoting nurse-led HIV screening into routine practice in inner-city practices with high HIV prevalence increased HIV testing, and may be associated with increased and earlier diagnosis. HIV screening in primary care should be considered a key strategy to reduce undiagnosed infection particularly among high risk persons not attending sexual health services. Funding: National Institute for Health Research ARC North Thames, and Barts and The London School of Medicine and Dentistry.